SUATU KAJIAN INDUSTRI TEPUNG TAPIOKA RAKYAT (ITTARA) - djumaali, djumaali (Badan Pengkajian dan Penerapan Teknologi, 2007)
Industri Tepung Tapioka Rakyat (ITTARA), is one policy product of Lampung Province Goverment. This program is suitable to Lampung potency as the cassava producer the cassava producer for raw material that reach 1.6 million tons per annum (1971). Lampung is the second biggest producer after Java. ITTARA is built to empowered civil economy in villagge with capacity average of 2 and 10 topioca flour tons. This study is fucused at 2 ton capacity because for 10 ton capacity are required big capital and relative expensive for all farmer. ITTARA is expected able to assist increasing prosperity of cassava so that the farmer alwasy in a weak possition. This study will cover technology used, the settlement of disposal and by product and other aspects.